FENOMENA GENDER DALAM PERILAKU TUTUR MENOLAK ETNIK MINANGKABAU MODERN - Hetti Waluati Triana (Kafa`ah: Journal of Gender Studies, 2016)
This article aims to explain that behavioral phenomena not only describe the linguistic behavior, but also a socio-cultural phenomenon as the language and expression are contributed and Influeced by the current condition. Therefore, the paradigm used sosiopragmatik conducted in informal situations with a focus on the behavior of said refuse ethnic Minangkabau in the domain of friendship. Data were collected using three data collection techniques based on the rules of conduct ethnographic said, namely observation, interview techniques,and techniques ethno-sciences (etno-pragmatik). The data were analyzed qualitatively and quantitatively in which the utterances are required to fulfill and explain the linguistic phenomenon appeared in the society. The results showed that through the said behavior quantitatively reject ethnic Minangkabau found the strength properties of the women. These finding showed the social changes in the practice of spoken atnik Minangkabau Modern. It could vary the sosiolinguistic sciences and may contribute  others.